Gómez Cardó, P.; Leão, D. F.; Oliveira, M. A. de, eds. (2014). Plutarco entre mundos. Visões de Esparta, Atenas e Roma, Humanitas Supplementum, Estudos Monográficos, Coimbra, Universidade de Coimbra, Coimbra University Press, Annablume Editora - Clúa Serena, Josep Antoni (Revista Archai, 2017)
resumo